2015
DOI: 10.1007/s00586-015-3920-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cement leakage by sequential PMMA application in a vertebroplasty model

Abstract: The sequential cement injection is a simple approach to minimize the risk for leakage. Taking advantage of the temperature gradient between body and room temperature, it is possible to increase the cement viscosity inside the vertebra while keeping it low in the syringe. Using sequential injection of small cement volumes, further leakage paths are blocked before further injection of the low-viscosity cement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Conversely, increasing the amount of cement injection may increase the incidence of cement leakage [11][12][13]. Clinical studies have shown that 70% of complications of vertebral body forming are associated with the cement leakage [14][15][16][17]. To overcome the shortcomings of PVP technology in the area of sufficient and symmetrical cement distribution, the flexible bone cement injector was designed to deliver bone cement at three zones in the vertebral body.…”
Section: Feasibility Safety and Clinical Efficacy Of Pvp With Flexibmentioning
confidence: 99%
“…Conversely, increasing the amount of cement injection may increase the incidence of cement leakage [11][12][13]. Clinical studies have shown that 70% of complications of vertebral body forming are associated with the cement leakage [14][15][16][17]. To overcome the shortcomings of PVP technology in the area of sufficient and symmetrical cement distribution, the flexible bone cement injector was designed to deliver bone cement at three zones in the vertebral body.…”
Section: Feasibility Safety and Clinical Efficacy Of Pvp With Flexibmentioning
confidence: 99%
“…In a standard model, leakage can be significantly reduced by the sequential application of small cement amounts. Possible leakage paths are blocked before reapplication of the low-viscous cement [35]. Moreover, the development of high-viscous PMMA cements have reduced the rate of cement leakages significantly, resulting in the disadvantage of the need for high-pressure injection devices that are more expensive and lack tactile feedback.…”
Section: Complicationsmentioning
confidence: 99%
“…The cement viscosity issue is also a crucial parameter that is associated with the risk of cement leakage [23,24]. Injecting PMMA at a low viscosity leads to a scattered, fingerlike, uncontrolled cement distribution pattern and, as a consequence, an increased chance of cement leakage.…”
Section: Introductionmentioning
confidence: 99%